The Impact of the Implementation of Sustainable Proklim Batik on Economic Empowerment and Environmental Conservation in Merbabu Asih 08, Cirebon City - tono, Tono Wartono; Darmun, Darmun (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama’ah, 2026)
Study purpose. This study aims to analyze the impact of the Batik Proklim Lestari program on economic empowerment and environmental preservation in Merbabu Asih 08, Larangan Harjamukti, Cirebon City. Materials and Methods. Using a qualitative case study approach, data was collected through in-depth interviews, observation, and documentation. Results. The study shows that this program provides double-track benefits. Economically, there has been a 15%-30% increase in artisans’ technical skills and income due to expanded market access for environmentally friendly products. Ecologically, the application of natural dyeing techniques and waste management has successfully reduced industrial pollution by 40%-50%. Conclusion. The sustainability of this program requires strengthening the natural raw material supply chain and adopting more efficient waste processing technologies.